Short communication: Vizilite®- A Non-Invasive Oral Cancer Screening Tool Using Chemiluminescent Technology; Does it's Use Make Sense? - Ghoshal, Dr. Nanda Kishore (Medical Science Journal for Advance Research, 2024)
Background: Early detection of oral cancer is crucial in improving survival rates. To improve early detection, the use of a dilute acetic acid rinse and observation under a ViziLite or chemiluminescent light (ViziLite; Zila Pharmaceuticals, Phoenix, AZ) has been recommended. Several screening techniques based on light interaction with tissue have been described to aid clinicians in the detection of early oral cancerous lesions. One of the most studied techniques is chemiluminescence. This method has been used in different studies but always by Oral Medicine specialists. Conclusion: Vizilite is a non-invasive screening technology widely used and best suited for clinicians with experiences, training and proven real time results, It is one of the modern device for oral cancer screening and consciousness, which has definite diagnostic value but limitations should be overcome by more confirmatory, sensitive, and specific tests.